BMT AS AN AGENT OF ECONOMIC TRANSFORMATION: A RANDOM EFFECTS ANALYSIS IN FORMER RED-LIGHT AREAS OF SURABAYA - Muhammad Abdul Rohman (I-Economics: A Research Journal on Islamic Economics)
This study aims to analyze the impact of the prostitution localization shutdown on the development of micro and small enterprises (MSEs) in Surabaya, focusing on policy interventions and the interaction with community-based microfinance institutions (BMTs). A quantitative method is employed using a random effect panel data regression on 154 urban villages from 2011 to 2021. The results reveal that the shutdown significantly reduced the number of MSEs, particularly in the food-beverage and textile sectors. However, the negative impact is substantially reversed when combined with BMT support. Social factors such as social capital and infrastructure access are also found to influence MSE dynamics. These findings highlight that localization shutdown policies should be followed by inclusive, community-based economic recovery strategies to mitigate the socioeconomic disruptions triggered by such closures.